Fair Mine Management in Indonesia - Hamid, Moh Ilias Bin; Angga, La Ode; Latupono, Barzah; Irham, Muhammad (PATTIMURA Law Study Review, 2025)
Environmental protection and management has consequences for the development of an integrated national policy system, and must be implemented in accordance with principles from the central government to the regions. Related to the above, Immanuel Kant thought that the principle of practical law comes from pure reason which is the basis for determining an action or deed. The type of research used is normative legal research, which is research that mainly examines positive legal provisions, legal principles, legal principles, and legal doctrines in order to answer the legal problems faced. This type of research is normative juridical, which is a legal research method that is carried out by reviewing literature or secondary materials. The form of legal rules related to equitable mining environmental management in Indonesia in the future should contain material that contains the following elements: a) integrated environmental management; b) clarity of authority between the central and regional governments; c) strengthening environmental control efforts; d) strengthening of pollution and/or environmental damage prevention instruments which include strategic environmental assessment instruments, spatial planning, environmental quality standards, environmental damage standard criteria, Environmental Impact Analysis, environmental management efforts and environmental monitoring efforts, licensing, environmental economic instruments, environment-based laws and regulations, environment-based budgeting, risk analysis environment, and other instruments in accordance with the development of science and technology; e) the use of licensing as a control instrument; f) the use of ecosystem approaches; g) certainty in responding to and anticipating global environmental developments; h) strengthening environmental democracy through access to information, access to participation, and access to justice as well as strengthening people's rights in environmental protection and management; i) Stricter enforcement of civil law, state administration, and criminal law; j) Strengthening institutions for more effective and responsive environmental protection and management; and k) Strengthening the authority of environmental supervisory officials and environmental civil servant investigators.